2014
DOI: 10.2215/cjn.08160813
|View full text |Cite
|
Sign up to set email alerts
|

Association of Kidney Function with Changes in the Endothelial Surface Layer

Abstract: Background and objectives ESRD is accompanied by endothelial dysfunction. Because the endothelial glycocalyx (endothelial surface layer) governs interactions between flowing blood and the vessel wall, perturbation could influence disease progression. This study used a novel noninvasive sidestream-darkfield imaging method, which measures the accessibility of red blood cells to the endothelial surface layer in the microcirculation (perfused boundary region), to investigate whether renal function is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
108
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 38 publications
(44 reference statements)
14
108
2
Order By: Relevance
“…33 Although we disclosed no significant increase in patients with stable CKD, our data are not necessarily contradictory to previous findings. Our CKD patients only had a moderate decline in renal function (mean eGFR 47 ml/min/1.73 m 2 ).…”
Section: Syndecan-1 and Long-term Mortality Ratescontrasting
confidence: 85%
See 1 more Smart Citation
“…33 Although we disclosed no significant increase in patients with stable CKD, our data are not necessarily contradictory to previous findings. Our CKD patients only had a moderate decline in renal function (mean eGFR 47 ml/min/1.73 m 2 ).…”
Section: Syndecan-1 and Long-term Mortality Ratescontrasting
confidence: 85%
“…In the cited study, and in accordance with our findings, patients with moderate kidney impairment after renal transplantation (eGFR 22 ml/min/1.73 m 2 ) presented with similar syndecan-1 levels when compared with controls. 33 More interesting is that the syndecan-1 level measured on ED admission has value as a predictor of acute worsening renal function during hospital stay, even after adjusting for other risk factors for AKI in this population, as suggested in other studies. 34 This finding merits consideration for 2 reasons: (1) the importance of glycocalyx damage on the pathophysiology of cardiorenal syndrome and (2) the use of syndecan-1 as a biomarker for the early detection of AKI.…”
Section: Syndecan-1 and Long-term Mortality Ratessupporting
confidence: 56%
“…Unfortunately, the long duration of the model, which was required to faithfully replicate changes seen in human diabetic nephropathy, precluded such follow-up studies in STZ-treated animals. This does not, however, detract from the fact that this study corroborates the rationale for the clinical use of ET A selective receptor blockade in diabetic nephropathy; given the systemic nature of loss of the glycocalyx in diabetes, it also provides a mechanism of action that can be monitored noninvasively (44) in patients before and during treatment.…”
Section: Discussionsupporting
confidence: 52%
“…We demonstrated that patients with renal failure have increased circulating levels of syndecan-1 and thrombomodulin, which was reversed by kidney transplantation (110). Furthermore, renal failure was shown to correlate with increased concentrations of shed hyaluronan (18). Altogether, while several glycocalyx components are shed upon endothelial activation, the exact location, mechanism, and timing of shedding is complex and mostly unknown.…”
Section: Studying the Endothelial Glycocalyxmentioning
confidence: 93%